Investigation on centrifugal pump performance degradation under air-water inlet two-phase flow conditions. Issue 3 (1st June 2018) - Si, Qiaorui; Cui, Qianglei; Zhang, Keyu; Yuan, Jianping; Bois, Gérard
Abstract : In order to study the flow characteristics of centrifugal pumps when transporting the gas-liquid mixture, water and air were chosen as the working medium. Both numerical simulation and experimental tests were conducted on a centrifugal pump under different conditions of inlet air volume fraction (IAVF). The calculation used URANS k-epsilon turbulence model combined with the Euler-Euler inhomogeneous two-phase model. The air distribution and velocity streamline inside the impeller were obtained to discuss the flow characteristics of the pump. The results show that air concentration is high at the inlet pressure side of the blade, where the vortex will exist, indicating that the gas concentration have a great relationship with the vortex aggregation in the impeller passages. In the experimental works, pump performances were measured at different IAVF and compared with numerical results. Contributions to the centrifugal pump performance degradations were analyzed under different air-water inlet flow condition such as IAVF, bubble size, inlet pressure. Results show that pump performance degradation is more pronounced for low flow rates compared to high flow rates. Finally, pressure pulsation and vibration experiments of the pump model under different IAVF were also conducted. Inlet and outlet transient pressure signals under four IAVF were investigated and pressure pulsation frequency of the monitors is near the blade passing frequency at different IAVF, and when IAVF increased, the lower frequency signal is more and more obvious. Vibration signals at five measuring points were also obtained under different IAVF for various flow rates.